"Bitch I Said Hi": The Bye Felipe Campaign and Discursive Activism in Mobile Dating Apps. (October 2016) - Shaw, Frances
This article examines the Instagram page for Bye Felipe, a feminist campaign where people submit screenshots of examples of harassment and sexual entitlement from men on online dating sites such as OKCupid and apps such as Tinder. I frame the campaign as an example of feminist discursive activism. The site owners collect contributions and aggregate examples of particular discursive patterns in hook up apps, in order to make collective political claims, a strategy that Tomlinson calls "intensification." I address the existing literature on cyber-misogyny and online harassment, and also research on previous similar campaigns such as Fedoras of OKCupid to discuss shaming as a political practice. I then draw out the patterns and concepts invoked in interventions and resultant discussions on Bye Felipe, examining the themes of rejection, silence and who has the right to silence, rape culture, and gendered sexual entitlement. I identify the political claims being made through the rhetorical strategies described in the first part of the article. Drawing on the work of McCosker on trolling as provocation, I discuss the role of repetition and rehearsal in the practice of discursive politics. Finally, through a discursive analysis of responses to the posts on Instagram and Facebook over time, I explore the ongoing and difficult boundary work around what constitutes appropriate examples for the site, and the articulation of feminist claims and discourses.